2021
DOI: 10.2298/tsci190510417d
|View full text |Cite
|
Sign up to set email alerts
|

A hydrodynamic criterion of alternative bubble departures

Abstract: The bubble departures from two neighbouring brass nozzles (with inner diameter of 1.1 mm) in three liquids: distilled water, mineral and synthetic engine oils were investigated. The numerical simulations were used for reconstruction of liquid flow around the departing bubbles. Bubble movements in liquid have been recorded using a high speed camera. The 2D bubble paths have been reconstructed using: Laplacian of Gaussian filters, algorithm of detection of local extremes of image brightness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The influence of the distance between needles on the interaction between bubbles departing from them was investigated in papers 15 , 16 . It was shown that the hydrodynamic interaction can lead to chaotic pressure changes in the gas supply system and consequently chaotic bubble departures 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the distance between needles on the interaction between bubbles departing from them was investigated in papers 15 , 16 . It was shown that the hydrodynamic interaction can lead to chaotic pressure changes in the gas supply system and consequently chaotic bubble departures 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the investigations on bubble departure, interactions between bubble-bubble and bubble coalescence are treated as an introduction to investigations on the greenhouse effect caused by escaping methane bubbles in the oceans [3,4]. There are a lot of papers in which the results of experiments of bubble generation from a single [5][6][7][8][9][10][11] and twin or more needles or orifices [12][13][14][15][16][17][18] were described.…”
mentioning
confidence: 99%
“…The influence of the distance between needles on the interaction between bubbles that departed from them was investigated in papers [12,13]. It was shown that the hydrodynamic interaction can lead to chaotic pressure changes in the gas supply system and consequently chaotic bubble departures [12].…”
mentioning
confidence: 99%
See 2 more Smart Citations